MicroRNA-552 expression in colorectal cancer and its clinicopathological significance - Joon Im; Soo Kyung Nam; Hye Seung Lee (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
Background MicroRNA-552 (miR-552) has been reported to correlate with the development and progression of various cancers, including colorectal cancer (CRC). This study aimed to investigate miR-552 expression in cancer tissue samples compared to normal mucosal tissue and its role as a diagnostic or prognostic marker in CRC patients. Methods Normal mucosal tissues and primary cancer tissues from 80 surgically resected CRC specimens were used. Quantitative real-time polymerase chain reaction was performed for miR-552 and U6 small nuclear RNA to analyze miR-552 expression and its clinicopathological significance. Immunohistochemistry for p53 and phosphatase and tension homolog (PTEN) was performed to evaluate their association with miR-552 expression. Results miR-552 expression was significantly higher in primary cancer tissues compared to normal mucosal tissues (p<.001). The expression level of miR552 was inversely correlated with that of PTEN (p=.068) and p53 (p=.004). Survival analysis showed that high miR-552 expression was associated with worse prognosis but this was not statistically significant (p=.255). However, patients with CRC having high miR-552 expression and loss of PTEN expression had significantly worse prognosis than others (p=.029). Conclusions Our results suggest that high miR-552 expression might be a potential diagnostic biomarker for CRC, and its combined analysis with PTEN expression can possibly be used as a prognostic marker.